Conversational Markers Used by Youth in Managua - Mairena Uriarte, Rosa Amanda (2018)
For this research work, a corpus of semi-guided interviews was created from the questionnaire proposed by the Project for the Sociolinguistic Study of Spanish in Spain and America (PRESEEA). The informants are young people between the ages of 18 and 34 who have completed high school, have grown up in the Monseñor Lezcano neighbourhood, one of the oldest in the municipality of Managua, and currently live in the same locality. From the transcripts of the recordings, the conversational markers of the oral discourse of the young people were identified with the help of Word Smith software, in order to classify them according to the proposal of Martín and Portolés (1999) in markers of epistemic modality, markers of deontic modality, focusers of otherness and conversational metadiscursives. Finally, the pragmatic functions of these discursive units were described.